Science teachers' data use practices: A descriptive analysis - Virginia Snodgrass Rangel; Carlos Monroy; Elizabeth Bell (Arizona State University, 2016)
There is a debate on students' low science achievement in the United States, particularly among low income, African American students, and Latino students. An important part of the education community's response to low achievement generally and in science specifically has been the implementation of high stakes accountability policies. Because of accountability's emphasis on educator data use, much research has examined different facets of it throughout educational organizations, but research has not focused on the extent to which data use might be content-specific. The purpose of this paper, then, was to investigate the data use practices of science teachers. Drawing from a broader study of science teachers in grades 5-8 across six school districts, this study reports results from teacher surveys and interviews. The findings indicate that while there were examples of science-specific data use, most of the science teachers used data in ways consistent with previous content-agnostic research. Implications for future research, policy, and practice are discussed.